Sustainable innovation revolutionises the concept of economic development - Zilli, Sandro (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The world is changing at an unprecedented speed: new technologies have become part of every aspect of our lives and activities, changing the way we do business, work, communicate, and changing the very role of people within society. The fourth industrial revolution has paved the way for the Digital Transformation and revolutionised the way we produce and organise work, bringing with it the need to rethink the relationship between man and technology, thus creating the preconditions for a 5.0 Society idea.